2022
DOI: 10.1097/aog.0000000000004867
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Immunoglobulin G Levels After the Pfizer-BioNTech Booster Dose for Coronavirus Disease 2019 (COVID-19) Vaccination During the Second Trimester of Pregnancy

Abstract: To evaluate maternal and neonatal severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) immunoglobulin G (IgG) antibody levels at birth after a third (booster) dose of the Pfizer-BioNTech messenger RNA (Pfizer) coronavirus disease 2019 (COVID-19) vaccine during the second trimester of pregnancy, and compare them with those in women who received two vaccine doses during the second trimester. METHODS:We conducted a prospective cohort study of women admitted to the delivery ward at a single center who rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
2
15
1
Order By: Relevance
“…Our results coincide with previous reports showing antibody levels among pregnant women to be significantly higher after the third dose compared to the second dose [19,20,26] and significantly higher after the second dose compared to recovered women [9,12,27]. Similar patterns were demonstrated in neonatal antibody levels [9,12,19,20,27].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results coincide with previous reports showing antibody levels among pregnant women to be significantly higher after the third dose compared to the second dose [19,20,26] and significantly higher after the second dose compared to recovered women [9,12,27]. Similar patterns were demonstrated in neonatal antibody levels [9,12,19,20,27].…”
Section: Discussionsupporting
confidence: 92%
“…Published reports have confirmed the enhanced humoral response of almost all patients to the third dose, especially in populations with a low humoral response or waning immunity after the first and second doses [28][29][30]. In pregnant women and their neonates, recent studies have shown that similar to the first and second doses of the BNT162b2 vaccine, the third dose is successful in generating a remarkable humoral immune response of SARS-CoV-2 IgG, as well as being safe [18][19][20]. Moreover, a Norwegian population-based cohort study suggested there was a lower risk of a positive test for SARS-CoV-2 during the first 4 months of life among infants born to mothers who were vaccinated during pregnancy [31].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The impact of immunization timing and vaccine dose on SARS‐CoV‐2 transplacental antibody transfer may influence neonatal seroprotection. According to previous studies, the COVID‐19 vaccine of pregnant women during the second trimester could be effective to achieve maternal protection and newborn safety during the pandemic 21,24,25 . In this study, we have found that the levels of SARS‐CoV‐2 antibodies were higher in infants from mothers immunizing the COVID‐19 vaccine than unvaccinated before pregnancy.…”
Section: Discussionmentioning
confidence: 50%
“…According to previous studies, the COVID‐19 vaccine of pregnant women during the second trimester could be effective to achieve maternal protection and newborn safety during the pandemic. 21 , 24 , 25 In this study, we have found that the levels of SARS‐CoV‐2 antibodies were higher in infants from mothers immunizing the COVID‐19 vaccine than unvaccinated before pregnancy. Although the level of SARS‐CoV‐2 IgG antibody decreased with the age of infants, significantly higher SARS‐CoV‐2 IgG antibodies levels in infants from the maternal 3‐dose of inactivated COVID‐19 vaccine before pregnancy compared with the 2‐dose.…”
Section: Discussionmentioning
confidence: 64%